Growth, Yield, Quality and Energetics of Mustard (Brassica juncea (L.) Czern & Coss) as Influenced by Weed Management and Sulphur Fertilization under Semi Arid Condition of Rajasthan - Kumar, Rajesh; Yadav, S. S.; Singh, Ummed; Verma, H. P. (International Journal of Bio-resource and Stress Management, 2021)
The field experiments were conducted during rabi (October to march) 2014–15 and 2015–16 at Agronomy farm, Jobner, Rajasthan, India to evaluate effect of weed management practices and sulphur fertilization on growth, yield and qualityof mustard (Brassica juncea (L.). The experimental field was laid out in a split plot design with seven treatments of weed management with four sulphur levels and three replications.Among weed control treatment crop dry matter at harvest stage (312.6 g-1 row length), maximum value of CGR and RGR during all the stages of crop growth, maximum seed yield (2493 kg ha-1), output energy (151500 MJ ha-1), output input energy ratio (13.65), Energy use efficiency (0.225) and energy balance (140430 MJ ha-1) was obtained with 2 HW at 25 and 45 DAS. Among the herbicidal treatment pendimethalin @ 0.75 kg ha-1 was next better treatment which was at par with one HW at 25 DAS. Among sulphur levels crop dry matter at harvest (222.3 g m-1 row length), maximum value of CGR and RGR during all the stages of crop growth, seed yield (2167 kg ha-1), oil yield (885 kg ha-1), oil yield (885 kg ha-1), output energy (135918 MJ ha-1), output input energy ratio (12.26), energy use efficiency (0.195 kg MJ-1) and energy balance (124856 MJ ha-1) were obtained with 60 kg S ha-1 which was at par with 40 kg S ha-1.